Lieux De Memoire Et Les Lieux De Rencontre: Sourb Karapet Dans Le Temoignage D’un Voyageur Armenien De La Pologne Du Xviieme Siecle - Košťálová, Petra (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
Long-standing tradition of ukht or sacred pilgrimage – multifaceted phenomenon which appeared not only in Armenian Apostolic Church of course – emerged already in first centuries after adoption of Christianity, developed throughout Middle Ages both in Armenia, Cilicia and worldwide Diaspora and finally reached its peak of popularity, followed by a certain decline (according to testimony of contemporary sources as Simeon of Poland) during 16th and 17th centuries. Simeons’ Travel Accounts show a certain decay of Armenian pilgrimmage to traditional sites as Rome and Santiago de Compostella, caused on the one hand by political instability in the region of Anatolia and Levant, on the other hand by lack of central authority (the fall of Cilician Kingdom in 1375, the transfer of Catholicosate back to Great Armenia in 1441, the „Isfahan capture“ of Armenian catholicoi at the very beginning of 17th century etc.). Nevertheless, the pilgrim status of sacred places as Jerusalem or more local sanctuaries as saint Karapet (Holy Precursor) near the town of Mush or Caesarea remained unchanged.
Keywords: Ottoman Empire